Fostering Innovation Through Business Digitalization to Support Business Sustainability - Adi Saputro; Selamet Riyadi; Dina Nadiyah; Slamet Mudjijah; Hary Kuswanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digitalization has become a transformative force reshaping how organizations innovate and sustain competitive advantages in an interconnected global economy. This study explores the intricate relationship between business digitalization, innovation capabilities, and sustainability outcomes. Employing a comprehensive literature review, it examines how digital transformation fosters innovative practices and supports sustainable business models. Key findings reveal that integrating digital technologies, such as artificial intelligence, IoT, and blockchain, significantly enhances innovation capacity by accelerating product development cycles, improving decision-making precision, and fostering collaborative innovation ecosystems. Moreover, digitalization optimizes resource utilization, minimizes environmental impact, and strengthens stakeholder engagement, contributing to measurable economic, environmental, and social sustainability outcomes. The synergy between digital transformation and sustainability initiatives provides organizations with strategic advantages, including improved operational efficiency, customer loyalty, and competitive positioning. However, challenges such as implementation barriers, balancing digital-sustainable priorities, and managing unintended environmental impacts persist. Future research should focus on empirical validation, industry-specific applications, and longitudinal studies to further elucidate the pathways through which digitalization supports sustainable innovation and long-term business resilience. This study underscores the imperative for organizations to strategically align digital transformation with sustainability objectives, ensuring their future success in a rapidly evolving business environment.